A more comprehensive approach offering instruments in one portal to facilitate higher uptake. (30th September 2020) - Rossmann, C; De Bock, F
Abstract: The good practice portal of the Federal Centre for Health Education (BZgA) consists of a nationwide collection of projects and interventions to promote the health of socially disadvantaged groups at community/setting level. An exchange platform (inforo) is also offered via the operating agency, although its use is still limited. The results of the evaluation of the platform suggest that the provision of practical projects and exchange of knowledge alone is not sufficient to support policy makers and practitioners who want to promote health in the community/setting. There is a need for advice on needs assessment, selection and appropriate implementation of health promotion measures. A comprehensive approach currently being tested in the field of activity promotion for older people is the provision of a web-based "toolbox" comprising the following tools: assessment instruments for analysing the need for health promotion measures, a user-friendly intervention/project database and broader evidence synthesis documents, as well as information on project management (organisational, legal, financial). Following the example of other best practice portals, a ranking methodology was developed to make the level of effectiveness of interventions visible and the evaluation requirements transparent. Evidence synthesis documents provide an entry point to learn more generally what works in a particular area of health promotion. In order to make the "toolbox" accessible to policy-makers and practitioners, information from previous studies was used in the development with regard to content and graphical presentation. BZgA is currently working on integrating evidence into the good practice portal. The evaluation of the toolbox in a small area of health promotion will provide initial insights into the inclusion of evidence and its added value. This presentation will conclude with a discussion of possibilities for improvement, challenges and limitations of this approach.